The Role Of Social Media In Building An Image and Communication At The Syubbanul Wathon Bandongan Magelang Islamic Boarding School - Muslikatun, Muslikatun; Siswanto, Siswanto (Prodi. Manajemen Pendidikan Islam, Fakultas Tarbiyah, Institut Pesantren Sunan Drajat, 2024)
This research aims to analyze the role of social media in shaping image and improving communication at the Syubbanul Wathon Islamic Boarding School, Bandongan, Magelang. Through a qualitative approach, this research explores how Islamic boarding schools utilize social media platforms such as Facebook, Instagram, TikTok and Twitter to present Islamic identity, educational activities, and strengthen interactions with the community. The research also highlights potential risks associated with social media use, such as sensitive issues and management of responses to negative comments. By understanding the role of social media in the context of Islamic boarding schools, this research is expected to provide insight into effective strategies in building a positive image and strong communication amidst developments in information technology. The results of this research are that the role of social media in the context of the Syubbanul Wathon Islamic Boarding School is not only limited to conveying information, but also involves forming a positive image and strengthening effective communication. The implications of these findings provide a deeper understanding of social media management practices in Islamic boarding schools and their relevance in the context of religious education in Indonesia.